2021
DOI: 10.1111/ejn.15565
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of carvacrol on beta‐amyloid‐induced impairments in in vitro and in vivo models of Alzheimer's disease

Abstract: Due to the complex nature of Alzheimer's disease (AD), it is important to investigate agents with multiple effects in the treatment of AD. Carvacrol possesses anti-acetylcholinesterase, anti-oxidant, and neuroprotective properties. We therefore investigated therapeutic effects of carvacrol on cell viability, oxidative stress, and cognitive impairment in Aβ1-42-induced in vitro and in vivo models of AD. SH-SY5Y cells differentiated into neurons by retinoic acid were pretreated with carvacrol or galantamine befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…To date, few studies have reported the neuroprotective effect of carvacrol. A recent study showed that carvacrol can increase the cell viability of differentiated SH-SY5Y cells and exhibited a protective effect against oxidative stress by preventing Aβ1–42-induced cytotoxicity, LDH release, and increments in malondialdehyde and H 2 O 2 levels in vitro [ 61 ]. Other literature data on the neuroprotective activity of carvacrol suggested that this compound can protect neuroblastoma SH-SY5Y cells against Fe 2+ -induced apoptosis [ 62 ] and reduces cadmium-triggered oxidative stress in PC12 cells and caspase-dependent and independent apoptosis [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have reported the neuroprotective effect of carvacrol. A recent study showed that carvacrol can increase the cell viability of differentiated SH-SY5Y cells and exhibited a protective effect against oxidative stress by preventing Aβ1–42-induced cytotoxicity, LDH release, and increments in malondialdehyde and H 2 O 2 levels in vitro [ 61 ]. Other literature data on the neuroprotective activity of carvacrol suggested that this compound can protect neuroblastoma SH-SY5Y cells against Fe 2+ -induced apoptosis [ 62 ] and reduces cadmium-triggered oxidative stress in PC12 cells and caspase-dependent and independent apoptosis [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevation of Glutathione and Glutathione Peroxidase in the presence of carvacrol in conjunction with the inhibition of the TRPM2 and TRPV4 channels act together to confer cellular protection against oxidative stress. The antioxidative nature of carvacrol and its therapeutic effects have been demonstrated in a mouse in vivo model of Alzheimer’s disease [ 42 ]. Intraperitoneal administration of carvacrol resulted in increased cellular viability in the experimental animal model of Alzheimer’s disease that uses Aβ1-42 bilateral intrahippocampal injection.…”
Section: Carvacrolmentioning
confidence: 99%
“…The potent free radical scavenging properties of OEO and thymol contribute to its ability to provide protection against chronic diseases and neurodegenerative diseases, as well as its potential as a preservative in food or nutraceuticals [ 89 , 90 , 91 , 92 , 93 ]. In a study conducted by Demir et al, the therapeutic efficacy of carvacrol in mitigating β-amyloid-induced damage in both in vitro and in vivo models of Alzheimer’s disease was assessed [ 94 ]. This study highlighted the anti-acetylcholinesterase, antioxidant, and neuroprotective properties of carvacrol.…”
Section: Bioactivity Of Essential Oils In Oregano Speciesmentioning
confidence: 99%